The system of financing of innovation and intellectual property capitalization (Journal of Economic Research & Business Administration, 2015)
One of the most difficult issues are the development of innovative financing innovative projects and commercialization of intellectual property. The paper It provides a method to solve them on the basis of mortgage securitization and not physical assets.